Images of language in middle english vernacular writings - CAWSEY, KATHY (D S BREWER, 2020)
An exploration of the use of images in Middle English texts, tracing out what can be deduced of a theory of language.
Keywords: English literature -- Middle English, 1100-1500 -- History and criticism.; Littérature anglaise -- 1100-1500 (Moyen anglais) -- Histoire et critique.; Philosophy of language.; LANGUAGE ARTS & DISCIPLINES / General.; English literature -- Middle English; 1100-1500; Chaucer.; Malory.; nightingale.; owl.; Electronic books.; Criticism, interpretation, etc.